Dynamic covalent chemistry of imines for the development of stimuli-responsive chitosan films as carriers of sustainable antifungal volatiles. (April 2022) - Heras-Mozos, Raquel; Hernández, Rebeca; Gavara, Rafael; Hernández-Muñoz, Pilar
Abstract: The aim of this work was to develop pH-responsive antifungal chitosan (CS) films based on the reversible bonding of the naturally occurring volatile aldehydes: cinnamaldehyde (CN), citral (CT) and their saturated derivatives hydrocinnamaldehyde (HC) and citronellal (CO) that have antifungal properties. Acid-catalyzed bonds were created by condensation of the carbonyl functional group of aldehydes with amino groups in CS films to yield imines which was confirmed by Attenuated Total Reflectance – Fourier Transform Infrared Spectroscopy (ATR-FTIR) and 13 C solid-state nuclear magnetic resonance ( 13 C NMR). α, β-unsaturated CN and CT were more reactive than their derivatives, reaching around 60% degree of substitution of aldehydes to chitosan films compared to 25% for HC and CO. Imines created with α, β-unsaturated aldehydes and aromatic HC remained quite stable at neutral pH. With regard to the hydrolysis of imines at pH 4, around 35% of anchored α, β-unsaturated aldehydes were lost, this value being 80% for HC whereas 100% of CO was lost after the first week of film immersion in buffered solution. The differences in the extent of hydrolysis of imine bonds depended on both the pH of the aqueous medium and also the chemical structure of the aldehyde. Curiously, it was observed α, β-unsaturated aldehydes exerted crosslinking effects on CS films since they did not disintegrate in water at pH 3. The crosslinking mechanism is discussed in the text. The antifungal activities of the developed films were tested against Penicillium expansum and Botrytis cinerea by the micro-atmosphere method using a double Petri dish system. Mold growth was completely inhibited by imine-CN-CS films activated at pH 4. Graphical abstract: Image 1 Highlights: A reversible grafting technique has been developed to anchor biocides in chitosan films. Reversible covalent bonds based on imines has been employed to stabilize volatile fungicides. Release of volatiles from chitosan films was triggered by pH.